The New Tools of Monetary Policy - Bernanke, Ben S. (American Economic Review, 2020)
To overcome the limits on traditional monetary policy imposed by the effective lower bound on short-term interest rates, in recent years the Federal Reserve and other advanced-economy central banks have deployed new policy tools. This lecture reviews what we know about the new monetary tools, focusing on quantitative easing (QE) and forward guidance, the principal new tools used by the Fed. I argue that the new tools have proven effective at easing financial conditions when policy rates are constrained by the lower bound, even when financial markets are functioning normally, and that they can be made even more effective in the future. Accordingly, the new tools should become part of the standard central bank toolkit. Simulations of the Fed’s FRB/US model suggest that, if the nominal neutral interest rate is in the range of 2–3 percent, consistent with most estimates for the United States, then a combination of QE and forward guidance can provide the equivalent of roughly 3 percentage points of policy space, largely offsetting the effects of the lower bound. If the neutral rate is much lower, however, then overcoming the effects of the lower bound may require additional measures, such as a moderate increase in the inflation target or greater reliance on fiscal policy for economic stabilization. (JEL D78, E31, E43, E52, E58, E62)